Will China and/or the United States Transform the WTO?. (2020) - Lester, Simon
Abstract : China's 2001 entry into the World Trade Organization (WTO) and the 2016 election of Donald Trump have converged to form an existential threat to the WTO. Can the WTO manage a large economy with China's level of state economic intervention and political authoritarianism? Will the Trump administration's confrontational approach reform or destroy the organization?